CARBON COMPOUNDS: Pollution Aspects - Khadka, Yagyarath (Patan Pragya, 2020)
Carbon is one of the major elements by which organic compounds cannot be imagined. Its compounds are very useful in human life as well as for nature. For example, carbon dioxide is used during photosynthesis in plants and CFCs is used in manufacturing of aerosol sprays and as refrigerants. In contrast, serious harmful effects are seen with over exposure or with increasing in level of its compounds. Use of carbon compounds awareness is necessary for its use in different purposes. Carbon monoxide and carbon dioxide released by the complete combustion of fossils and by automobile exhaust causes carbon pollution along with other various causes. Reuse and recycling of carbon compounds minimizes its pollution. Carboxy hemoglobin formed by combination of carbon monoxide with red blood cell is also more fatal. As we know, different gases formed due to the combination of carbon with other elements causes various changes like climate change, destruction of heritage goods (acid rain), different human risk, flooding etc. So, pollution of carbon should be managed before it causes any huge harmful effects. Finally, carbon related pollution leads to global warming, greenhouse effects, ozone layer depletion, ocean acidification, acid rain, climate change and also fatal to human beings.